Teacher training and pedagogical practices: a significant look at the contributions of Mario Osorio Marques (Revista Contexto & Educação, 2025)
The purpose of this study is to explore issues related to the legacy of Mario Osorio Marques' work in the field of education, based on publications and legal documents that discuss teaching, permeating its influence on teacher training and pedagogical practices. A qualitative research approach was adopted, focusing on documentary and bibliographical analysis. Data collection was based on the careful selection of excerpts and quotations from the works analyzed, followed by a critical interpretation. For this, the content analysis technique was used, as proposed by Bardin (2011). The results indicate the defense of continuous teacher training and contextualized and inclusive teaching that continues today, influencing educational policies and inspiring educators to see pedagogical practice as an ethical and political commitment. Therefore, by rescuing and reflecting on the contributions of Marques' works that still shape education in Brazil, it reaffirms the relevance of his ideas for the development of transformative and democratic educational practices.
Keywords: Teacher training; Educational practices; Brazilian education